Pengaruh Budaya Organisasi, Modal Intelektual, dan Perilaku Inovatif Terhadap Kinerja Pemimpin Jurusan di Universitas Negeri Medan - Purba, Sukarman (KINERJA, 2009)
The objective of this research is to obtain information concerning the effect of organizational culture, intellectual capital, innovative behavior, on Department chairman’s performance. The research was carried out in 2005 with sample of 40, selected randomly and the data has been analyzed by path analysis after all variables put into the correlation matrix. The finding of the research shows that Department chairman’s performance is affected directly by Organizational culture, Intellectual capital, and Innovative behavior. Based on those findings it could be concluded that any changing or variation which occurred at Department chairman’s performance might have been effected by Organizational culture, Intellectual capital, and Innovative behavior. Therefore, in managing Department chairman’s performance, organizational culture, intellectual capital, and innovative behavior should be put into strategic planning of human resources development at Universitas Negeri Medan, however other variables are necessary to be taken into account by next performance research.